An evaluation of the importance of marketing activities for export success of smaller sized New Zealand companies : a thesis prepared in partial fulfillment of the requirements for the degree of Master of Business Studies at Massey University - Chaney, Isabella Mary (Massey University, 1993)
Various authors, including Porter, have emphasised the need for exporters to pursue activities that can gain a competitive advantage for the New Zealand export business. However, it is important to determine which of those activities are responsible for enhancing export performance. Of relevance to marketers are the marketing components which are more important in international marketing. Thus, this study tested the hypothesis that there is a positive relationship between marketing activities of planning, information search for opportunities, product adaptation and export success for smaller New Zealand companies. Export success was defined as the ratio of export sales to total sales. Exporters were also classified as per their level of export performance and differences in marketing strategies identified. To test the hypothesis, a sample of 320 small to medium sized New Zealand exporters was randomly selected from the four product categories of food (excluding meat), apparel, building and electrical. This selection of industries enabled analysis by both consumer and industrial groups. The results indicated that export intensity can be explained in terms of planning, information search and to a lesser extent product adaptation. In particular, information is a vital asset for exporters. The key appears to be maintaining contact with the export market in the form of company personnel travelling on fact finding missions or exhibiting products at overseas trade fairs. The marketing activity which showed a significant difference between high and low performing exporters was planning. The time involved and also the resources allocated to this activity by high performers demonstrated their commitment to exporting. Overall, this study has demonstrated the importance of certain marketing activities in terms of export success. If New Zealand smaller sized companies are prepared to lay the foundations for their export business in terms of planning and information gathering, then sustainability in New Zealand's export drive may be achieved. Knowledge is of two kinds. We know a subject ourselves, or we know where we can find information upon it. Samuel Johnson, 1709-1784 from Boswell, Life of Johnson, 1763.
Keywords: Export marketing; Marketing; New Zealand